An appeal for a code of conduct for marine conservation. (July 2017) - Bennett, Nathan J.; Teh, Lydia; Ota, Yoshitaka; Christie, Patrick; Ayers, Adam; Day, Jon C.; Franks, Phil; Gill, David; Gruby, Rebecca L.; Kittinger, John N.; Koehn, J. Zachary; Lewis, Nai'a.; et al.
Abstract: Marine conservation actions are promoted to conserve natural values and support human wellbeing. Yet the quality of governance processes and the social consequences of some marine conservation initiatives have been the subject of critique and even human rights complaints. These types of governance and social issues may jeopardize the legitimacy of, support for and long-term effectiveness of marine conservation. Thus, we argue that a clearly articulated and comprehensive set of social standards - a code of conduct - is needed to guide marine conservation. In this paper, we draw on the results of an expert meeting and scoping review to present key principles that might be taken into account in a code of conduct, to propose a draft set of foundational elements for inclusion in a code of conduct, to discuss the benefits and challenges of such a document, and to propose next steps to develop and facilitate the uptake of a broadly applicable code of conduct within the marine conservation community. The objectives of developing such a code of conduct are to promote fair conservation governance and decision-making, socially just conservation actions and outcomes, and accountable conservation practitioners and organizations. The uptake and implementation of a code of conduct would enable marine conservation to be both socially acceptable and ecologically effective, thereby contributing to a truly sustainable ocean. Highlights: Poor governance and social issues can jeopardize the legitimacy of, support for and long-term effectiveness of marine conservation. A comprehensive set of social standards is needed to provide a solid platform for conservation actions. This paper reviews key principles and identifies next steps in developing a code of conduct for marine conservation. The objectives of a code of conduct are to promote fair, just and accountable marine conservation. A code of conduct will enable marine conservation to be both socially acceptable and ecologically effective.